SYRIZA : the failure of the populist promise - Mudde, Cas (Springer, 2020)
Contents: Foreword; Petros Papasarantopoulos.-Part 1. SYRIZA's Populist Illusions.-Part 2. Cas Mudde's Interviews about Right and Left Populism, Radicalism, Extremism and SYRIZA.-Part 3. About Liberal Democracy and Extremism.-Addendum: The Books' Journal Colloquium about Populism.